Exploring the Employment of the Informal Sector in Indonesia and the Factors that Influence It - Ahsan Pramana Desanta; Siti Aisyah (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The informal sector holds a significant position in Indonesia's labor structure, particularly as a response to the limited availability of formal job opportunities. The increasing proportion of informal workers reflects a shift in labor market patterns influenced by diverse economic and social factors. This study examines the impact of the Open Unemployment Rate (OUR), Average Years of Schooling (AYS), Provincial Gross Regional Domestic Product (GRDP), Regional Minimum Wage (RMW), and poverty rate on informal employment. Adopting a descriptive quantitative method, the research utilizes secondary data sourced from Statistics Indonesia (BPS) and the Ministry of Manpower (Kemnaker) for the years 2019 to 2023. The analysis applies panel data regression, with the Fixed Effect Model (FEM) determined as the most appropriate technique. Findings indicate that the open unemployment rate, poverty rate, and minimum wage positively and significantly affect informal sector employment, while GRDP has a negative and significant effect. Meanwhile, average years of schooling do not significantly impact informal labor absorption. The study suggests that the government should focus on boosting regional economic growth to lower informal employment reliance and strengthen the formal labor market's competitiveness.